LionBarat App: Augmented Reality-Based Fashion Shopping Application - Aufar Aufar; Faris Naufal Adiputra; Ismu Johan Halim (Universitas Komputer Indonesia, 2023)
The purpose of this study is to design a mobile-based application that serves to help potential buyers to easily find fashion according to the wishes of potential buyers accurately. The research method used in this study is a descriptive method of analysis with a qualitative approach. Meanwhile, the application development process uses an object-oriented approach with the System Development Life Cycle Prototyping. The results of the research method on the LionBarat application are expected to provide convenience in shopping for fashion without fear that the clothes that will be purchased are not suitable because of the greatness or are different from those in the application user interface. The main concept of this application is a way to make it easier for potential buyers to find the right and accurate fashion according to what the LionBarat application displays. This idea was created from the unrest of online shopping application users who buy clothes such as clothes, pants or shoes due to the lack of accurate images and descriptions of existing products. In addition, this application has features that are integrated with Google Lens and Lidar so that application users can search and buy the desired fashion by inputting/scanning images into the search field. The conclusion of designing this application can be concluded that fashion sales on the application can be even better if it can take advantage of the implementation of Google Lens and Augmented Reality (AR)technology as an online fashion shopping feature. This research is expected to help fashion sellers in getting more potential consumers who can indirectly increase new innovations in online shopping.